POST-PNEUMONECTOMY SYNDROME IN ADULT PRESENTING WITH RECURRENT SYNCOPE - Gigovska Dimova, Irena; Ristovski, Vladimir; Prgova Veljanova, Biljana; Buklioska Ilievska, Daniela; Eftimovska-Otovic, Natasa; Nedeska Minova, Natasa (Journal of Morphological Sciences; Vol 5 No 3 (2022): JMS, 2022)
Post-pneumonectomy syndrome is a rare, late complication of pneumonectomy, caused by a mediastinal shift, rotation and deviation of the remaining lung into the contralateral hemithorax, most commonly resulting in symptomatic central airway compression.  Case report:  Recurrent syncope following a left pneumonectomy was described in a 63 year-old man, forty years after the initial treatment. Four years physician visit including the family doctor, a neurologist, neurosurgeon, physiatrist, radiologist, psychiatrist and finally a cardiologist made the diagnosis hard to establish and the treatment delayed. The post-pneumonectomy syndrome is a complex constellation of symptoms, following previous lung pneumonectomy, with various presentations mimicking different pathologies. Its diagnosis is often misleading, making the treatment and prognosis hard to predict.  Keywords: post-pneumonectomy syndrome, pneumonectomy, syncope, prosthesis implantation, mediastinal repositioning.